Pediatric bronchiolitis obliterans after Stevens-Johnson syndrome: A multidisciplinary case report - Atmaja, Birgitta Suparman Supa; Setyoningrum, Retno Asih; Chafid, Arda Pratama Putra; Hapsari, Rika; Violetta, Lenny (Acta Biomedica Atenei Parmensis, 2025)
Introduction: Bronchiolitis obliterans (BO) is a rare, severe obstructive pulmonary disease characterized by irreversible small airway fibrosis. Pediatric BO secondary to Stevens-Johnson syndrome (SJS) presents unique diagnostic and therapeutic challenges, often mimicking other respiratory diseases such as asthma. This case emphasizes the complexities of BO diagnosis and management in children. Case Report: A 5-year-old boy presented with progressive respiratory symptoms following SJS triggered by antiepileptic medication and meropenem. Initial management as severe asthma failed, prompting further investigations. High-resolution computed tomography (HRCT) revealed mosaic attenuation consistent with BO. Bronchoscopy findings of white plaques and subcutaneous emphysema supported the diagnosis, although invasive lung biopsy was avoided due to critical condition. The clinical course was complicated by multidrug-resistant Pseudomonas aeruginosa and Acinetobacter baumannii infections, requiring aggressive antimicrobial therapy. Despite multidisciplinary care, including anti-inflammatory treatment, oxygen support, and nutritional interventions, the patient succumbed to respiratory failure, underscoring the progressive nature of BO. Results: This case highlights the importance of early recognition and differentiation of BO from asthma in pediatric patients, particularly those with SJS. Advanced imaging and a multidisciplinary approach were pivotal in diagnosis and management. The challenges faced in this case emphasize the need for standardized protocols and tailored care strategies, particularly in resource-limited settings. Conclusions: This report illustrates the clinical complexity of BO secondary to SJS, underscoring the importance of vigilant monitoring, multidisciplinary management, and the development of improved diagnostic and therapeutic strategies to optimize outcomes.